Lactic acid bacteria in fermented foods of Indonesian origin - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
In this study, about 194 lactic acid bacteria strains have been isolated from 21 kinds of fermented foods (plant materials and fish origin). These fermented foods were salted-fermented fruits, vegetables & fish